2007
DOI: 10.1124/dmd.106.014522
|View full text |Cite
|
Sign up to set email alerts
|

The Disposition of Prasugrel, a Novel Thienopyridine, in Humans

Abstract: ABSTRACT:Prasugrel, a prodrug, is a novel and potent inhibitor of platelet aggregation in vivo. The metabolism of prasugrel and the elimination and pharmacokinetics of its active metabolite, 2-[1-[2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4-mercapto-3-piperidinylidene]acetic acid (R-138727), three inactive metabolites, and radioactivity were determined in five healthy male subjects after a single 15-mg (100 Ci) Clopidogrel and ticlopidine are thienopyridine prodrugs that are activated in vivo to pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
148
1
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 10 publications
9
148
1
6
Order By: Relevance
“…A recent study by Schneider et al demonstrated a transient recovery in platelet function in patients with stable coronary artery disease during the transition from cangrelor to prasugrel but this effect was limited if prasugrel was administered 30min before the end of cangrelor infusion [17]. These observations from pharmacodynamic studies are consistent with the known pharmacokinetic profiles of thienopyridine AMs and cangrelor [7][8][9][10][11] and our current findings: it is only when cangrelor plasma levels fall sufficiently for cangrelor to dissociate from the P2Y 12 receptor that thienopyridine AMs are able to bind to the receptor. Consequently, in order for clopidogrel and prasugrel to achieve irreversible inhibition of the P2Y 12 receptor, cangrelor plasma levels must fall sufficiently (via hydrolysis to inactive metabolite) before thienopyridine AM levels fall to ineffective levels as a result of distribution to extravascular compartments.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A recent study by Schneider et al demonstrated a transient recovery in platelet function in patients with stable coronary artery disease during the transition from cangrelor to prasugrel but this effect was limited if prasugrel was administered 30min before the end of cangrelor infusion [17]. These observations from pharmacodynamic studies are consistent with the known pharmacokinetic profiles of thienopyridine AMs and cangrelor [7][8][9][10][11] and our current findings: it is only when cangrelor plasma levels fall sufficiently for cangrelor to dissociate from the P2Y 12 receptor that thienopyridine AMs are able to bind to the receptor. Consequently, in order for clopidogrel and prasugrel to achieve irreversible inhibition of the P2Y 12 receptor, cangrelor plasma levels must fall sufficiently (via hydrolysis to inactive metabolite) before thienopyridine AM levels fall to ineffective levels as a result of distribution to extravascular compartments.…”
Section: Discussionsupporting
confidence: 77%
“…Clopidogrel active metabolite has a distribution phase plasma half-life of approximately 30 minutes and prasugrel's active metabolite demonstrates a similar profile [8,9,10] with plasma levels of both falling rapidly to less than 0.1 mol/L in the first four hours during the distribution phase [11]. Due to the irreversible binding of the thienopyridine active metabolites to platelet P2Y 12 receptors, the inhibitory effects of clopidogrel and prasugrel persist long after the relatively short-lived active metabolites have been cleared from plasma, and normal platelet function is not restored for up to 7 days post dose.…”
mentioning
confidence: 99%
“…The pharmacokinetic properties of prasugrel and clopidogrel have been investigated in several studies and are summarized in Table 2. 12,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] In contrast to clopidogrel, [43][44][45] genetic variants in CYP 2C19 genes have not been shown to affect the antiplatelet response to prasugrel. …”
Section: Current Recommendations For Thienopyridines As Add-on Antiplmentioning
confidence: 99%
“…55 This conclusion was derived from an analysis of pharmacy and medical claims in the Medco Solutions database for 9,862 patients who received a PPI, compared with 6,828 patients who did not receive a PPI following a percutaneous coronary intervention (PCI). The Society for Cardiovascular Angiography and Interventions issued a statement on May 6, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]58 Prasugrel…”
Section: Clinical Profile Of Prasugrelmentioning
confidence: 99%
“…Differences in the effect of CYP3A4 on the metabolism of these two drugs may account for these differences. 4,5 The second issue is whether atorvastatin, which binds to but has not been reported to inhibit CYP3A4, can also modulate the therapeutic effect of thienopyridine. The effect reported by Dr. Farid and colleagues is equivocal for clopidogrel and negative for prasugrel.…”
mentioning
confidence: 99%